Domestic financing of HIV prevention interventions: a mixed methods study of the ability to pay (ATP) and willingness to pay (WTP) for voluntary medical male circumcision in Uganda - John Bekiita Byabagambi; Mark Limmer; Bruce Hollingsworth (Journal of Global Health Economics and Policy)
# Background External funding supports the HIV and AIDS response in Sub-Saharan Africa, but reducing this dependence is vital for longer-term sustainability. This study examined the ability and willingness to pay for voluntary medical male circumcision (VMMC) in Uganda as a potential funding source for domestic HIV prevention services. # Methods A mixed-methods study design structured around economics and planned behaviour theories was used. Data were collected through phone interviews, with quantitative data analysed using regression and qualitative data via reflexive thematic analysis. # Results A total of 454 participants were recruited for the quantitative study and 29 for in-depth interviews. 85% had the ability to pay, and 76% expressed willingness to pay for VMMC. Key influencing factors included age, education, religion, rural residence, and perceived behavioural control. # Conclusions Study participants demonstrated substantial ability and willingness to pay for VMMC. Fee-for-service programs should address the economic and attitudinal factors influencing ATP and WTP.